IMPLEMENTASI KEBIJAKAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI DAERAH KHUSUS IBUKOTA JAKARTA: IMPLEMENTATION OF LAND AND BUILDING TAX COLLECTION POLICY FOR RURAL AND URBAN AREAS (PBB-P2) IN THE SPECIAL CAPITAL REGION OF JAKARTA - Juliarini, Aniek; Karunia, Luki; Misra (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
This study analyzes the implementation of the PBB-P2 (Land and Building Tax for Rural and Urban Areas) collection policy under the Financial Relations Law between the Central and Regional Governments (HKPD Law) in DKI Jakarta in 2024. DKI Jakarta was selected due to the complexity of its tax objects and subjects, its significant revenue potential, and its role as a policy reference for other regions. The analysis covers the determination of NJOP, NJOPTKP, NJKP, PBB-P2 rates, and fiscal incentives, examined through communication aspects (transmission, clarity, and consistency) and policy substance (responsiveness to diverse target groups and expected behavioral changes). The study uses a concurrent embedded method with a primary qualitative approach supported by data triangulation and focus group discussion (FGD). The findings show that NJOP adjustments apply only to non-village objects; NJOPTKP is IDR 60 million; NJKP is 40% for residential and 60% for non-residential properties; and the PBB-P2 rate is 0.5%. Fiscal incentives—such as relief, reductions, discounts, installments, and penalty waivers—effectively ease taxpayers’ burdens while maintaining revenue. PBB-P2 revenue reached IDR 9.938 trillion, growing 10.31% from 2023, becoming the largest regional tax and contributing over 50% to local revenue (PAD). Communication is generally effective, though grassroots education and NIK matching (57%) need improvement. This study offers a best practice model for other local governments.